Pre-Commercial Thinning Loblolly Pines – Does It Pay? - Rick A. Williams; Kimberly Bohn; Justin McKeithen (EDIS)
FOR-188, a 5-page illustrated fact sheet by R. A. Williams, K. Bohn, and J. McKeithen, describes methods and silvicultural and economic benefits for reducing tree density before the trees reach merchantable size. Includes references. Published by the UF School of Forest Resources and Conservation, June 2008.